Reduction of Crosstalk Distortion in 5G - Relaxed Isolation-based Linearization for sub-6 GHz Advanced Antenna Systems - Abdalrahman, Fida; Al-Qamaji, Ali (My University, 2019)
Increasing demand for higher data rates in wireless communication systems has tremendously evolved over the last years. This demand is rapidly increasing with rising in number of wireless devices. Advanced antenna systems (AAS) – known as massive MIMO – is one of the central enabling radio technologies for 5G cellular systems that significantly increase the data rates provided for data-hungry applications. A fundamental component in the realization of multiple antenna systems is the radio frequency (RF) power amplifier (PA) at each transmitter branch. The reason for its crucial role is because it takes the responsibility of amplifying the transmitted signal to suitable power levels for transmission. These RF PAs are the most power-hungry components in RF transmitters. Consequently, their energy efficiency is a major concern. One way to increase the PA efficiency is by increasing the input signal power to the PA. However, the signals, using modern modulation schemes, e.g., Orthogonal Frequency Division Multiplexing (OFDM) and Wideband Code Division Multiple Access (W-CDMA), have high Peak to average power ratio (PAPR). Hence, PAs introduce nonlinear distortion to the amplified signal. This nonlinear behavior of PAs does not only distorts the transmitted signal (in-band distortion), but also produces spectral regrowth which causes interference to the other signals in neighboring channels (out-band distortion). Due to these distortions, 3GPP spectrum regulations might be violated in terms of in-band and out-band distortions. Hence, PAs are required to be linear and highly efficient. To do so, some linearization technique can be used, like Digital Pre-distortion (DPD) to linearize the PA behavior. Massive MIMO systems contains up to several hundreds of antennas, and these antennas are closely attached. This complicates the transmitter structure, and the smaller space between antenna elements increases the cross-talk between them due to mutual coupling. In addition to that, there is impedance mismatch between the power amplifier and the antenna at each radio branch. As a consequence, these multiple antenna systems are suffered from nonlinear distortion due to the combining effects of mismatch and cross-talk at the output of PA, in addition to the non-linear distortion from PA itself at high PAPR. To avoid both mismatch and cross-talk coupling effects, expensive and bulky isolators should be placed between PAs and antennas, which increase system design complexity and cost. Hence, the project main aim is to relax the isolation requirement, while applying linearization technique (DPD), to save the cost, complexity and reduce the design requirements in base stations. In this project, the DPD is implemented as a linearization technique, using a behavioral model of PA that counts for PA non-linearity and cross-talk, while mismatch effects is not considered. Further investigations are carried out to test different levels of isolation to know up to which extent the isolation can be relaxed while keeping the Adjacent Channel Leakage Ratio (ACLR) level of -50 dBc, due to 3GPP regulations. These investigations led to a conclusion that, in sub-6 GHz, it would be impossible to relax the isolation level if the PA model that does not count for cross-talk coupling is used. In contrast, when counting for cross-talk coupling in the PA behavioral model, isolation level is relaxed to about 11 dB while keeping the targeted ACLR level.